K--g Cupid in the corner - playing Bopeep. - Elmes, William (active 1797-1814) (Benbow, 1820)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; George IV, King of Great Britain, 1762-1830